2019
DOI: 10.1073/pnas.1907849116
|View full text |Cite
|
Sign up to set email alerts
|

Three archetypical classes of macromolecular regulators of protein liquid–liquid phase separation

Abstract: Membraneless organelles, corresponding to the droplet phase upon liquid–liquid phase separation (LLPS) of protein or protein–RNA mixtures, mediate myriad cellular functions. Cells use a variety of biochemical signals such as expression level and posttranslational modification to regulate droplet formation and dissolution, but the physical basis of the regulatory mechanisms remains ill-defined and quantitative assessment of the effects is largely lacking. Our computational study predicted that the strength of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
156
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 116 publications
(184 citation statements)
references
References 43 publications
28
156
0
Order By: Relevance
“…As support for the forgoing classification of regulators, using pentamers of SH3 domains and proline-rich motifs (SH35 and PRM5) as driver proteins 50 , we found Ficoll, lysozyme, and heparin as representatives of volume-exclusion promotors, weak-attraction suppressors, and strong-attraction promotors 51 . This work highlights regulator-driver interaction strength as a key determinant for regulatory effects on thermodynamic 7 properties of phase separation.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…As support for the forgoing classification of regulators, using pentamers of SH3 domains and proline-rich motifs (SH35 and PRM5) as driver proteins 50 , we found Ficoll, lysozyme, and heparin as representatives of volume-exclusion promotors, weak-attraction suppressors, and strong-attraction promotors 51 . This work highlights regulator-driver interaction strength as a key determinant for regulatory effects on thermodynamic 7 properties of phase separation.…”
Section: Introductionsupporting
confidence: 54%
“…In our previous study 51 , we determined H as a strong-attraction promotor of S:P phase separation. Correspondingly, at S:P equimolar ratio, increasing H initially leads to a decrease in the S and P threshold concentration for phase separation but, upon a further increase in concentration, H switches from a promotor to a suppressor and hence the S and P threshold concentration starts to increase ( Fig.…”
Section: Ternary Phase Diagrams Unveil Relative Strengths Of Pairwisementioning
confidence: 99%
See 2 more Smart Citations
“…More and more studies suggested that many cellular metabolic processes are regulated by LLPS, so are some intractable diseases such as ALS (amyotrophic lateral sclerosis) [4] and AD (Alzheimer disease) [5]. A number of proteins have been verified to be able to form liquid-like membraneless assemblies in cells and in vitro [3,[6][7][8][9]. Meanwhile, studies indicated that RNA can regulate the LLPS of proteins and influence the formation of bio-molecular condensates [10].…”
Section: Introductionmentioning
confidence: 99%